Review of the Malagasy Anthobosca, the Bizarre and the Sublime (Hymenoptera: Tiphiidae: Anthoboscinae) - Kimsey, Lynn S. (Zootaxa, 2009)
The Malagasy tiphiids in the genus Anthobosca are revised, with description of eight new species, including fisheri, harinhalai, mahajangaensis, castanea, namorokaensis, nigrimacula, toliaraensis and hallucigenia spp. nov. There are fourteen described species of Anthobosca recorded from Madagascar including the new ones below. A key to species, distribution maps and illustrations are given.